Respuesta :
Answer:
6
Step-by-step explanation:
First, we'll need to remove the parentheses: 3 - 5h = -18h + 81.
Then, we will move the variable to the left-hand side and change its sign, giving us 3 - 5h + 18h = 81
Then we must collect like terms, giving us 13h = 81 - 3
Finally, to get our answer, we must divide both sides of the equation by 13, giving us the answer of 6.
Answer:
[tex]4 - 1 - 5h = 9( - 2h + 9) \\ 3 - 5h = - 18h + 81 \\ 18h - 5h = 81 - 3 \\ 13h = 78 \\h = \frac{78}{13} \\ \therefore \: h = 6[/tex]